2010
DOI: 10.1007/s00056-010-0908-9
|View full text |Cite
|
Sign up to set email alerts
|

Primary Failure of Eruption (PFE) – Clinical and Molecular Genetics Analysis

Abstract: Knowledge of the genetic causes of non-syndromic PFE can now be used for the differential diagnosis of eruption failure. It permits affected family members to be identified early and may lead to new treatment possibilities in the long term. The genetically-verified diagnosis of "primary failure of eruption" can protect patients and orthodontists from years of futile treatment, because orthodontic treatment alone does not lead to success. Moreover, it has a negative influence on unaffected teeth and areas of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 27 publications
4
26
0
9
Order By: Relevance
“…It was speculated to be familial in nature (Frazier-Bowers et al, 2007), but the cause was unknown until recently, where the causative gene was identified as PTHR1 (Decker et al, 2008). While the true incidence of PFE is unknown, it has been estimated to occur in approximately 0.6% of the population (Stellzig-Eisenhauer et al, 2010).…”
mentioning
confidence: 99%
“…It was speculated to be familial in nature (Frazier-Bowers et al, 2007), but the cause was unknown until recently, where the causative gene was identified as PTHR1 (Decker et al, 2008). While the true incidence of PFE is unknown, it has been estimated to occur in approximately 0.6% of the population (Stellzig-Eisenhauer et al, 2010).…”
mentioning
confidence: 99%
“…Second mandibular molar was only involved in 5% of the cases, retention of mandibular first and second molars are extremely rare and odontomas suggest to be the only cause (14). In our case mandibular second molar was missing and the impacted tooth assumed as the third molar by considering its crown and root formation.…”
Section: Discussionmentioning
confidence: 63%
“…Au niveau chirurgical, des ostéotomies subapicales peuvent être réali-sées. En cas d'échec, les avulsions des dents atteintes de DPE provoquent d'importants défauts osseux, une greffe osseuse sera alors nécessaire en cas de solution implantaire [5,28,29]. On peut également s'interroger sur la possibilité d'avulsion et d'autotransplantation dentaire à distance.…”
Section: Discussionunclassified